Sabbath as resistance : saying no to the culture of now - Brueggemann, Walter (Westminster John Knox Press, 2014)
"DIscussions about the Sabbath often center around moralistic laws and arguments over whether a person should be able to play cards or purchase liquor on Sundays. In this book, popular author Walter Brueggemann writes that the Sabbath is not simply about keeping rules but rather about becoming a whole person and restoring a whole society. Importantly, Brueggemann speaks to a 24/7 society of consumption, a society in which we live to achieve, accomplish, perform, and possess. We want more, own more, use more, eat more, and drink more. Brueggemann shows readers how keeping the Sabbath allows us to break this restless cycle and focus on what is truly important: God, other people, all life. He offers world-weary Christians a glimpse of a more fulfilling and simpler life through Sabbath observance." -- back cover